Development of true-stress creep model through analysis of constant-load creep data with application to finite element methods. (December 2014) - Connolly, M.; Whittaker, M.; Williams, S.
<x content-type="archive" xml:space="preserve">Abstract</x> The creep behaviour of the nickel superalloy RR1000 is studied through a number of constant-load creep tests. It is often assumed that creep data generated by constant-load testing are unsuitable for building a generalised creep model due to the non-constant stresses incurred. Analysis of existing models shows that significant errors may occur in many approaches, which attempt to recreate the strain evolution with time. A model is presented which is not reliant on time as a parameter and is therefore able to utilise constant-load creep data without enforcing the assumption of a constant stress. This model is demonstrated through numerical analyses to replicate the creep behaviour across a large range of stresses accurately. The proposed model is then adapted as an Abaqus user-subroutine to demonstrate capability within finite element analysis.